2000
DOI: 10.1042/bj3460217
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cGMP-dependent mesangial-cell relaxation: a role for myosin light-chain phosphatase activation

Abstract: Although the cGMP-dependent relaxation of contractile cells seems to depend on the ability of the cyclic nucleotide to interfere with intracellular calcium, this does not appear to be the only mechanism involved. The present experiments were designed to analyse alternative mechanisms, trying to test the hypothesis that cGMP could relax rat mesangial cells by activating myosin light-chain phosphatase (MLC-PP), with the subsequent dephosphorylation of myosin light chain (MLC). The effect of a cGMP analogue, dibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Every cell with a sharp margin suitable for the planimetric analysis was considered, and 6-12 cells were analyzed per photograph. Planar cell surface area (PCSA) was determined by computer aid planimetric techniques (17,35). Measurements were performed by two different researchers in a blind fashion.…”
Section: Methodsmentioning
confidence: 99%
“…Every cell with a sharp margin suitable for the planimetric analysis was considered, and 6-12 cells were analyzed per photograph. Planar cell surface area (PCSA) was determined by computer aid planimetric techniques (17,35). Measurements were performed by two different researchers in a blind fashion.…”
Section: Methodsmentioning
confidence: 99%
“…2 Recent studies in other preparations also challenged the classical model of action for NO. 4,6,19,20 However, the cellular mechanism of NO-induced, Ca 2ϩ -independent dilations in microvessels remains unclear. Wu et al 3 demonstrated Ca 2ϩ -independent relaxations by 8-Br-cGMP in skinned rabbit ileum smooth muscle that were based on activation of MLCP.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, cGMPdependent relaxations of mesangial cells were also shown to depend on MLCP activation. 4 Recently, Surks et al 5 provided a possible molecular basis demonstrating that cGKI␣, which finally mediates the effects of NO and cGMP, is targeted to the contractile apparatus by a leucine zipper interaction with the MLCP myosin-binding subunit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PKG can decrease cytosolic calcium by increasing calcium efflux and calcium uptake into the sarcoplasmic reticulum [21,22]. PKG can also induce vasodilatation by decreasing myofilament calcium sensitivity through phosphorylation of proteins such as telokin [23,24], myosin light chain phosphatase [24,25], Rho kinase [26] and possibly SM22-· [27].…”
Section: Introductionmentioning
confidence: 99%